Respostas
respondido por:
1
s=s0+v0.t+1/2^.g.t^2
s= 0+0+1/2.10.t^2
s=5.t^2
no t1= S1=5.t^2
t2= s2= 5(2t)^2 = 20t^2
t3= s3= 5(3t)^2= 45t
S 3 - S 2= 6,25 -> 45t^2 - 20t^2 = 6,25 ->
25.t^2 = 6,25
t^2= 6.25/25
t= rais quadrada de 0,25 s
S4= h = 5(4.t)^4 = (5).(16).(0,25)= 20m
s= 0+0+1/2.10.t^2
s=5.t^2
no t1= S1=5.t^2
t2= s2= 5(2t)^2 = 20t^2
t3= s3= 5(3t)^2= 45t
S 3 - S 2= 6,25 -> 45t^2 - 20t^2 = 6,25 ->
25.t^2 = 6,25
t^2= 6.25/25
t= rais quadrada de 0,25 s
S4= h = 5(4.t)^4 = (5).(16).(0,25)= 20m
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás